PENGARUH PENERAPAN ALUR MERDEKA TERHADAP KEMAMPUAN LITERASI FINANSIAL SISWA DI KELAS V - Al Ihsan, Mauli; Syamsuyurnita, Syamsuyurnita; Sari, Suci Perwita; Nasution, Ismail Saleh (STKIP PGRI Situbondo, 2024)
The aim of this research is to determine the effect of implementing the independent flow on students' financial literacy abilities. Financial literacy is an understanding and skills regarding understanding concepts, risks and context in financial matters. The research uses quantitative methods where this research uses and collects systematic and structured data from the beginning to the end of data collection. The total population studied was 8 samples with the sample being in class V North Gombak DICTIONARY Study Studio, Selangor, Malaysia. The research was based on students' lack of understanding of financial literacy, so they were unable to manage their finances wisely. This lack of understanding is due to a lack of education regarding financial literacy in both formal and non-formal education. The results of this research show that the application of the independent flow to students' financial literacy skills is very influential and can provide students with an understanding and skills regarding financial literacy which can be seen from the T-Test Sig 2 Tailed = 0.000 < 0.05 which is stated to be very influential, so it can be concluded that the application The independent flow is very influential on the development of students' abilities in terms of student financial literacy and can be applied in the learning process.